Effectively training community supervision officers: a meta-analytic review of the impact on offender outcome - Chadwick, Nick (Criminal justice and behavior, 2015)
The development and implementation of training programs aimed at increasing community supervision officers? use of core correctional practices served as the focus of this review. Studies that evaluated the effect that officer training had on offender outcome were included in the review. Based on 10 studies (N = 8,335), this meta-analysis found that when offenders were supervised by officers who received training in core correctional practices, they demonstrated reductions in recidivism (odds ratio [OR] = 1.48) compared with those offenders supervised by the status quo. The results support further use of such training programs and emphasize the benefit to public safety as well as the fiscal savings that can result from sound implementation. However, this was an initial review, and further research is needed to confirm and extend these findings.